Experiment study on warm ring rolling of 52100 bearing steel coupling microstructure spheroidisation. (2017) - Qian, Dongsheng; Yang, Jun; Mao, Huajie; Hua, Lin
Abstract: As an advanced rotary forming technology, ring rolling is an important application in bearing ring manufacturing. Spheroidising annealing is necessary for ring rolling of 52100 bearing ring because of the cold working requirement, but its long processing period results in high energy consumption, low productivity and poor surface quality. In this work, based on the favourable effects of divorced eutectoid transformation and plastic deformation on microstructure spheroidisation, a warm ring rolling method for 52100 bearing steel was proposed and expected to directly realize the spheroidisation by ring rolling, and experimental studies were carried out to testify its feasibility. Firstly, warm comprehension experiment of 52100 steel was performed on Gleeble-3500 thermo-simulation system to pre-evaluate the spheroidisation effect in warm deformation. Then, warm ring rolling experiment of 52100 bearing steel was conducted on ring rolling mill. The experimental results show that the effective spheroidisation with finer carbide particles and acceptable microhardness compared to regular spheroidizing annealing were obtained under both of warm comprehension and warm ring rolling with suitable deformation conditions. The experimental study verified that warm ring rolling of 52100 bearing steel coupling microstructure spheroidisation is feasible, it can be potentially as a new ring rolling method for 52100 bearing ring with the advantageous of energy saving, efficiency increasing and procedure shortening.